(untitled) (American International Journal of Economics and Finance Research, 2019)
This study examined the effect of capital structure on profitability of listed insurance firms in Nigeria for the period 2013-2017 The study used correlation research design. The source of data which were collected from the published annual financial reports of studies listed insurance firms in Nigeria. The population of the study comprised of the 28 listed insurance firms. The sample size was fifteen (15) listed insurance firms in Nigeria. The data collected were analyzed with the aid of OLS multiple regression technique. Using 75 firm-year paneled observations, the result of the ordinary least square regression showed that short-term debt has a negative and significant effect on the profitability of listed insurance firms in Nigeria. In addition, long-term debt has a positive and significant effect on profitability. Finally, premium growth has positively significant effect on profitability of listed insurance firms. Based on the findings, the study recommends that the management of listed insurance firms should strive towards having optimum capital structure by increasing their equity level and reducing dependence on debts so as to avoid being cash strapped and debt ridden.